â€œValidasi Data Kependudukanâ€ Apps as A Representation of Sustainable Public Governance - Nulhaqim, Soni Akhmad; Deliarnoor, Nandang Alamsah; Putri, Taqiya Arini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The era of digitalization has brought improvement and progress in various facets of public life, particularly in the aspect of public governance sustainability. However, as a social phenomenon, digitization in the governance process is inseparable from the population and civil registry conflicts which are intertwined. As a narrow practical example, the implementation of Validasi Data Kependudukan Apps in the Nanggerang Village of Sumedang Regency represents the empirical occurrence that digitalization represented by the Apps in the realm of public governance does not operate as expected, on the other hand, population and civil registry conflicts arise over the presence of the application implementation and its policies. This study aims to examine the application of â€œValidasi Data Kependudukanâ€ in Nanggerang Village, Sumedang Regency as a social phenomenon representing sustainable public governance. A qualitative descriptive method with interview and empirical observation are conducted asÂ  analytical tool. In a conclusion, this study reveals that the existence of a Validasi Data Kependudukan Apps is the impact of the digitalization process in the government and is a derivative of the application that has been implemented in Sumedang Regency. Throughout the implementation process, there are problems with public awareness related to the existence of this application, causing conflicts between the government and the community itself in terms of managing population documents. Accommodation is an obstacle to existing awareness problems and has an impact on the ideals of sustainable public governance.